A risk score for prediction of venous thromboembolism in gynecologic cancer: The Thrombogyn score. Issue 5 (28th May 2020) - Norris, Lucy A.; Ward, Mark P.; O'Toole, Sharon A.; Marchocki, Zibi; Ibrahim, Nadia; Khashan, Ali S.; Abu Saadeh, Feras; Gleeson, Noreen
Abstract: Background: Gynecologic cancers are associated with high rates of venous thromboembolism (VTE), which is exacerbated by pelvic surgery and chemotherapy. Objectives: The aim of this study was to develop and validate a risk score for VTE in patients with gynecologic cancer and to test the predictive ability of the score following addition of procoagulant biomarker data. Patients and methods: Clinical and laboratory variables were used to develop a risk score for the prediction of VTE in patients with gynecological cancer (n = 616), which was validated in a separate cohort of patients (n = 406). Endogenous thrombin potential and D‐dimer levels were determined in a subset (n = 290) of patients and used to produce an extended score in the validation cohort. Results: Multivariable regression analysis identified BMI >30, hemoglobin <11.5 g/dL and chemotherapy as independent predictors of VTE, which formed the Thrombogyn score. Following competing risk regression analysis, subdistribution hazard ratios (SHRs), adjusted for cancer stage, were 8.16 (95% confidence interval [CI], 1.69‐43.77) in the high‐risk group (score = 2‐3) and 4.12 (95% CI, 0.85‐20.15) in the intermediate‐risk group (score = 1) compared with the low‐risk group (score = 0). SHRs for the validation cohort were 6.26 (95% CI, 1.24‐31.39) and 3.00 (95% CI, 0.67‐13.32), respectively. Cumulative incidence of VTE in the validation cohort high‐risk group was 10.34% (95% CI, 6.51‐16.41) per women‐years compared with 1.06% (95% CI, 0.26‐4.26) in the low‐risk group. Using the extended Thrombogyn score, adjusted SHRs were 16.83 (95% CI, 4.20‐67.37) in the high‐risk group with a cumulative incidence of 21.15% (95% CI, 10.32‐45.24). External validation of the score is required. Conclusions: The Thrombogyn score identifies patients with gynecologic cancer at high and low risk of VTE. Addition of biomarker data improves the predictive power of the score.